Value chain transformation: Taking stock of WorldFish research on value chains and markets - Kruijssen, Froukje; Audet-Belanger, G.; Choudhury, A.; Crissman, C.C.; Dalsgaard, Jens Peter T.; Dawson, C.; Dickson, M.; Genschick, S.; Islam, M.M.; Kaminski, A.; Keus, H.J.; McDougall, Cynthia; et al. (CGIAR Research Program on Aquatic Agricultural Systems, 2016)
The goal of WorldFish’s research on markets and value chains is to increase the benefits to resource-poor people from fisheries and aquaculture value chains by researching (1) key barriers to resource-poor men, women and other marginalized groups gaining greater benefits from participation in value chains, including barriers related to the availability, affordability and quality of nutrient-rich fish for resource-poor consumers; (2) interventions to overcome those barriers; and (3) mechanisms that are most effective for scaling up of value chain interventions. This paper aims to promote and document learning across WorldFish’s value chain research efforts in Asia and Africa. It has three main objectives: (1) to take stock of WorldFish’s past and ongoing research on value chains; (2) to draw out commonalities and differences between these projects; and (3) to provide a synthesis of some learning that can guide future work.